2021
DOI: 10.1186/s13041-020-00726-x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-17 induced by cumulative mild stress promoted depression-like behaviors in young adult mice

Abstract: The number of young adult patients with major depression, one of the most common mental disorders, is gradually increasing in modern society. Stressful experiences in early life are considered one of the risk factors for chronic depressive symptoms, along with an abnormal inflammatory response in later life. Although increased inflammatory activity has been identified in patients with depression, the cause of long-lasting depressive states is still unclear. To identify the effects of cumulative mild stress in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 61 publications
8
46
0
Order By: Relevance
“…In clinical studies, higher IL-17 levels were associated with anhedonia severity in men, but not in women [44,45]. Our results are also consistent with previous reports that the increase in IL-17 level, including Th17 cells, was associated with depressionlike behavior in rodent models [46,47]. Conversely, serum IL-1β, IL-6, and CRP levels significantly increased only in the female group with MDD compared with those in the ageand sex-matched controls.…”
Section: Discussionsupporting
confidence: 92%
“…In clinical studies, higher IL-17 levels were associated with anhedonia severity in men, but not in women [44,45]. Our results are also consistent with previous reports that the increase in IL-17 level, including Th17 cells, was associated with depressionlike behavior in rodent models [46,47]. Conversely, serum IL-1β, IL-6, and CRP levels significantly increased only in the female group with MDD compared with those in the ageand sex-matched controls.…”
Section: Discussionsupporting
confidence: 92%
“…Finally, in vitro addition of serotonin and treatment of MDD patients with selective serotonin reuptake inhibitors (SSRIs) reduced the production of Th17/Tc17-related cytokines by CD4+= and CD8+ T cells ( 60 ). Treatment of depressed mice with anti-IL-17 mAb inhibits glial differentiation and ameliorates anxiety and depression behaviors ( 61 ). In the human setting, CD4+CD25+ Tregs are found decreased in patients with major depression ( 62 ) ( Figure 1 ).…”
Section: Il-17 Levels and Th17 Cell Subsets In Patients With Depressionmentioning
confidence: 99%
“…A hypothesis based on the assumption that microglia activation is pivotal for the increase of pro-inflammatory cytokines such as IL-16 and TGF-b, which polarize CD4+ T cells towards Th-17 is formulated. Experimental data suggest that anti-IL-17 mAb treatment, diminishes IL-17 induction and Th-17 differentiation and ameliorates anxiety and depression-like behaviors ( 61 ) (prepared with BioRender).…”
Section: Il-17 Levels and Th17 Cell Subsets In Patients With Depressionmentioning
confidence: 99%
“…Recently, progressive multiple sclerosis model caused depression- and anxiety-like behaviors, which has been found simultaneously upregulation of IL-17 and GFAP in the hippocampus but not prefrontal cortex [ 45 ]. The recent study also reported that cumulative mild stress promoted depression-like behaviors in young adult mice and specifically upregulated IL-17 expression in the hippocampus [ 46 ]. We then further verified whether lipocalin 2 expression in RSDS was reduced by EA stimulation.…”
Section: Resultsmentioning
confidence: 99%